Parameter Adaptive Terminal Sliding Mode Control of Flexible Coupling Air-Breathing Hypersonic Vehicle - Haibing Chen; Wei Lin; Tielin Ma; Hengxian Jin; Cheng Xu (International Journal of Aerospace Engineering)
The highly nonlinear and coupling characteristics of a flexible air-breathing hypersonic vehicle create great challenges to its flight control design. A unique parameter adaptive nonsingular terminal sliding mode method is proposed for longitudinal control law design of a flexible coupling air-breathing hypersonic vehicle. This method uses adaptive reaching law gain instead of the additional adaptive compensation term to handle the uncertainty to improve robustness. The stability of the close loop system is proved via a Lyapunov way. The longitudinal tracking control law for velocity and angle of attack is designed based on a rigid dynamic model of a flexible air-breathing hypersonic vehicle. A strong coupling model of the same vehicle, considering aerodynamic-scramjet engine-flight dynamic-elastic couplings, is established as the verification platform of the designed control law. The remarkable differences of flight dynamic characteristics between this strong coupling model and the rigid body model can be seen, which mean the controller needs to endure very great uncertainty, unmodeled dynamics, and other types of internal disturbance. Simulation results based on the coupling model demonstrate that the designed control law has good performance and acceptable robustness.